APPLICATION OF FLIPPED CLASSROOM LEARNING MODELS WITH PEER INSTRUCTION FLIPPED TYPE TO IMPROVE THE MATHEMATICAL PROBLEMS SOLVING ABILITY OF PRE-PROSPEROUS STUDENTS - Angra Meta Ruswana (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
This research was motivated by the low mathematical problem solving abilities. The aims of this research are to examine and describe the differences between pre-prosperous students who used flipped classroom learning models with peer instruction flipped type  and pre-prosperous students who used conventional learning in the improvement of students’ mathematical problem solving abilities. This research was conducted in class XI of SMK Taruna Bangsa, Ciamis. The research used  Quasi-Experiment method by using instrument in the form of mathematical problem solving ability test to obtain the research data. Data analysis was conducted on normalized gain of two sample groups by using the normalized gain difference test. The result showed there were the differences between pre-prosporous students who used flipped classroom learning model with peer instruction flipped type and students who used conventional learning in the improvement of students’ mathematical problem solving abilities